Medieval Multilingual Manuscripts Case Studies from Ireland to Japan - Mhaonaigh, Máire Ní; Clarke, Michael (Studies in Manuscript Cultures, 2022)
Medieval manuscripts combining multiple languages, whether in fusion or in collision, provide tangible evidence for linguistic and cultural interactions. Such encounters are documented in this volume through case studies from across Europe and Asia, all the way from Ireland to Japan, exploring the creativity of medieval language use as a function of cross-cultural contact and fluidity in this key period of nation-formation (9th-14th centuries CE).